Study of component structural equivalent fatigue based on a combined stress gradient approach and the theory of critical distance. (February 2016) - Sun, Song-song; Yu, Xiao-li; Chen, Xiao-ping
Abstract: Fatigue limit load is one of the most important factors and concerns in designing and manufacturing critical mechanical parts such as crankshafts. Traditionally, this governing parameter is obtained via a time and money-consuming experiment and analysis of a simple structure while it becomes theoretically complicated for sophisticated cases. In this paper, proper extrapolation methods to calculate the stress gradient in the stress concentration area are first chosen to obtain the material parameter using the theory of critical distance (TCD) indirectly. Then the fatigue limit load of crankshafts with the same material properties but different structures are computed. Validation between the prediction and the experimental results shows that this combined approach may provide a more satisfactory result in terms of fatigue limit for quick engineering prediction. Graphical abstract: Highlights: Application of the theory of critical distance (TCD) in complicated shaped engineering structures (crankshaft). Calculation of the stress gradient of complex structures in its stress concentration area. Experimental verification for the prediction result.